The Turkish version of the pregnancy physical activity questionnaire: cross-cultural adaptation, reliability, and validity - Ekin, Atalay; Tosun, Gokhan; Solmaz, Ulas; Mat, Emre; Gezer, Cenk; Malkoc, Mehtap; Tosun, Ozge Celiker; Mutlu, Ebru Kaya; Adiyeke, Mehmet; Okyay, Emre (Journal of Physical Therapy Science, 2015)
[Purpose] The aim of this study was to translate the Pregnancy Physical Activity Questionnaire, adapt it for use with Turkish subjects and determine its reliability and validity. [Subjects and Methods] The Pregnancy Physical Activity Questionnaire was translated into Turkish and administered twice at 7–14-day intervals to pregnant women to assess the test-retest reliability. Cronbach’s α was used for internal consistency, and the inter-rater correlation coefficient was used to calculate the test-retest reliability. The Turkish Short Form 36 Health Survey (SF-36) and the International Physical Activity Questionnaire were used to estimate validity. [Results] The internal consistency during the first and third trimesters of pregnancy was excellent, with Cronbach’s α values of 0.93 and 0.95, respectively. The mean interval between the two assessments was 11.1 ± 2.1 days. The correlation coefficient between the total activity measured by the Turkish version of the Pregnancy Physical Activity Questionnaire and the International Physical Activity Questionnaire estimates of the total metabolic equivalent were fair to poor during the first, second, and third trimesters of pregnancy (r = 0.17, r = 0.17, r = 0.21, respectively). The Turkish version of the Pregnancy Physical Activity Questionnaire showed fair correlations with the Short Form 36 Health Survey physical component score (r = −0.30) and mental component score (r = −0.37) for the first trimester of pregnancy. [Conclusion] The Turkish version of the Pregnancy Physical Activity Questionnaire was found to be reliable and valid for assessing a pregnant woman’s physical activity.